Synthesis of new derivatives of Ceftazidime as possible Prodrugs - M. Alwan, Shakir; H. Abdul-Wahab, Abdul-Hafeedh (Iraqi Journal of Pharmaceutical Sciences, 2017)
Five new ceftazidime derivatives were designed and synthesized in an attempt to improve the acid stability and may increase the spectrum of ceftazidime. The synthesized compounds included; Schiff base of ceftazidime (compound 1), ceftazidime lysine amide Schiff base (compound 2), ceftazidime lysine amide (compound 3), ceftazidime-di-lysine amide Schiff base (compound 4) and ceftazidime-di-lysine amide (compound 5). New ceftazidime derivatives were successfully prepared characterized and identified using spectral and elemental microanalysis (CHNS) analyses and the results comply with the calculated measurements.Compounds 1 and 2 were subjected to a stability study in phosphate buffer (0.2M, pH 7.4) and in KCl/HCl buffer (0.2M, pH 1.2) at different time intervals (0 â€“ 240 min) incubated at 37 Â°C. This revealed that both compounds in phosphate buffer (0.2M, pH 7.4) are significantly stable with t 1/2 of 18hrs and 24hrs respectively. However, compounds 1 and 2 are less stable in KCl/HCl buffer (0.2M, pH 1.2) with t1/2 of 3.48hrs and 3.13hrs respectively.The antibacterial evaluation of the new ceftazidime derivatives showed various degrees of antibacterial activities when compared with ceftazidime. The chemical modifications of ceftazidime showed slight effect on activities and most of compounds retained the antibacterial activities. Compounds 2 and 4 afforded comparable antibacterial action. However, compounds 3 and 5 were equipotent with ceftazidime with respect to E.coli and Staph. aureose. Compound 4 has better activity than ceftazidime with respect to Pseudomonas aeruginosa. Schiff's base derivative of lysine (2, 6-bis-(benzylideneamino) hexanoic acid) gave a reasonable antibacterial action towards Escherichia coli and Streptococcus Spp; as compared with lysine which has no antibacterial activity.Key words: Ceftazidime, Schiff bases, Lysine.